The Cost of Asking: ‘Say that Again?’: A Social Capital Theory View Into How Lecture Recording Supports Widening Participation - MacKay, Jill R. D.; Nordmann, Emily; Murray, Leigh; Browitt, Alison; Anderson, Monika; Hutchison, Jacqui (Frontiers in Education, 2021)
Lecture recording, as a form of technology enhanced learning, has been purported to support equality in Higher Education. The introduction of lecture recording is often controversial, with some lecturers having concerns as to how recordings may change teaching and learning. A commonly reported motivation for incorporating lecture recordings is supporting the needs of widening participation students, students who are otherwise under-represented in higher education. In this study, we used focus groups to explore the experiences of widening participation students in higher education as they navigated their university programmes. We held four focus groups in three Scottish universities, and discussed and developed findings alongside a stakeholder group. We then applied a social capital lens to the data to explore whether recordings can be used to overcome a lack of social capital in widening participation students. Our participants identified areas where they lacked social ‘credit’, such as a lack of peer parity among colleagues and experiences which could be described as microaggressions. Students discussed reasons why the ‘cost’ of asking questions in class was too high, and how recordings support them by allowing them to save on this perceived cost. However students also recognised the tension of a lack of trust between lecturers and students, which could be exacerbated by recordings. We found good evidence to support a social capital view of ‘trust as credit’ in interactions between students and lecturers, and provide suggestions for how lecture recording can be used to support widening participation students in this area.